Evaluation of functional outcomes and complications following modified Latarjet reconstruction in athletes with anterior shoulder instability. Issue 3 (July 2015) - Colegate-Stone, Toby J; van der Watt, Christelle; de Beer, Joe F
Background: The optimal management of anterior shoulder instability in athletes continues to be a challenge. The present study aimed to evaluate the functional outcomes of athletes with anterior shoulder instability following modified Latarjet reconstruction through assessing the timing of return to sport and complications. Methods: Retrospective assessment was performed of athletes ( n = 56) who presented with recurrent anterior shoulder instability and were treated with modified congruent arc Latarjet reconstruction over a 1-year period. Rugby union was the predominant sport performed. Pre-operative instability severity index scores were assessed. Postoperative complications were recorded as was the time taken for the athlete to return to sport. Results: Arthroscopic evaluation revealed that 86% of patients had associated bony lesions affecting the glenohumeral joint. The overall complication rate relating to the Latarjet reconstruction was 7%. No episodes of recurrent shoulder instability were noted. Of the patients, 89% returned to competitive sport at the same level as that prior to surgery. The mean time post surgery to returning to full training was 3.2 months. Conclusions: The modified congruent arc Latarjet procedure facilitates early rehabilitation and return to sport. These results support our systematic management protocol of performing modified Latarjet surgery in contact sport athletes with recurrent anterior instability.